Antimicrobial activity of diverse chemotypes of Lippia graveolens against Aeromonas hydrophila isolated from tilapia - García-Pérez, Josué (2023)
Objetive: This study aimed to evaluate the antimicrobial efficacy of essential oil (EO) from diverse chemotypes of Lippia graveolens against oxytetracycline-resistant Aeromonas hydrophila, which primarily affects the tilapia aquaculture (Oreochromis sp) in Guatemala. Methodology: L. graveolens were collected in three departments in Guatemala, the EO was obtained by hydrodistillation and characterized by gas chromatography and mass spectrometry (GC/MS). Subsequently, an antimicrobial assay was conducted by screening the disk and dilution susceptibility tests, and evaluation of synergistic interactions among the chemotypes, each test being carried out in triplicate. Results: The analysis revealed the presence of twenty-seven compounds in the EO obtained from the chemotypes, the main class being monoterpene. The major constituents identified were cis-Dihydro-β-terpineol (8.84%) in chemotype I, carvacrol (51.82%) in chemotype II, and thymol (79.62%) in chemotype III. All EO chemotypes of L. graveolens demonstrated the ability to inhibit the A. hydrophila growth. Thymol chemotype exhibited the strongest inhibitory effect against bacterial growth, with a minimum inhibitory concentration (MIC) of 92.4 µg/mL and a minimum bactericidal concentration (MBC) of 184.8 µg/mL. Furthermore, the results suggest that there is no synergistic or additive effect when combining different chemotypes of L. graveolens. Conclusions: This the first report of L. graveolens chemotypes exhibiting antimicrobial activity against oxytetracycline-resistant A. hydrophila. The findings suggest the chemotype thymol could be a potential treatment for infections in the tilapia aquaculture in Guatemala.